Asymmetrical layered assemblies of graphene oxide for programmable actuation devices. (20th October 2020) - Huang, Yuehua; Li, Junjun; Xiang, Yi; Li, Nanfeng; Li, Fengji; Yang, Tingting
Abstract: Asymmetrical structures are known to have many unique properties. They are preferred to be applied in many fields, especially in graphene oxide (GO)-based membrane actuators. Assembling GO with other materials layer by layer and post-processing a single piece of GO membrane are two effective strategies to construct asymmetrical structures. However, the above researches are built on a prerequisite that the single piece of GO membrane is regarded as homogeneous. We have now discovered a long-overlooked actuation behavior of pure GO membrane. This pure GO membrane was prepared by vacuum filtration and showed originally asymmetrical structure. Such GO membrane responded to infrared light and relative humidity change with considerable bending angle. The origin of the asymmetrical structures and their actuation mechanism have been discussed in detail. The asymmetrical interlamellar spacing and non-smooth surface morphologies of GO membrane synergistically lead to the actuation behavior. Moreover, the actuation performance could be easily regulated by adding polydopamine to control the interaction between GO sheets. This finding has wide implications in designing programmable bending devices such as microrobot, biomimetic claw and smart finger. This work exhibits great potential for application in soft robotics.